Microarchaeological Study of the Achaemenid Throne Legs from the Israel Museum Collection - Pagelson, Yarden (Tel Aviv, 2020)
An investigation of the three Achaemenid throne parts housed in The Israel Museum, Jerusalem, reported to be from Samaria, found that they were made of bronze but with ceramic material that adhered to their interior. The purpose of the study was to determine their provenance, provenience and manufacturing techniques. As museum pieces, this had to be done in a minimally destructive manner. The methods employed were pXRF, SEM-EDS and petrography. All three items were cast from a leaded high-tin copper alloy, using the lost wax technique. However, the artefacts were cast in two workshops, neither of which was in the Samaria region. In conjunction with their Achaemenid characteristics, it is likely that the thrones were manufactured as part of the Achaemenid imperial policy, thus, granting royal credence to the individual occupying the throne, perhaps the governor of a province.